Environmental DNA barcoding reveals general biodiversity patterns in the large tropical rift Lake Albert - Bálint, Miklós; Tumusiime, Julius; Nakintu, Justine; Baranski, Damian; Schardt, Leonie; Romahn, Juliane; Dusabe, Marie-Claire; Tolo, Casim Umba; Kagoro, Grace Rugunda; Ssenkuba, Francis; Junginger, Annett; Albrecht, Christian; et al. (My University, 2024)
Lake Albert, Africa's seventh-largest lake and a biodiversity hotspot, faces significant environmental challenges, including unregulated anthropogenic pressure and a lack of comprehensive biological studies. To address the scarcity of biodiversity data, we utilized environmental DNA (eDNA) metabarcoding to assess the lake's eukaryotic and metazoan communities. Surface water samples were collected at three distinct locations: close to the southern inflow of the Semliki River, the central part of the lake, and close to the northern inflow of the Victoria Nile and outflow of the Albert Nile. We aimed to study ecological patterns across the lake, focusing on sequence variant richness and community composition, testing for differences among locations and between shoreline and pelagic zones. Consistent with previous morphology-based observations, our results revealed differences in community composition among the three sites, with cyclopoid copepods dominating the communities. Distance from shore was a significant factor influencing community composition, confirming expectations about the effects of nutrient and oxygen availability gradients. However, the lack of comprehensive reference sequence data limited accurate taxonomic assignments. Despite these limitations, our study demonstrates that eDNA metabarcoding is highly useful for assessing biodiversity in underexplored tropical freshwater ecosystems. We advocate for urgent efforts to generate reference sequences from tropical regions to enhance the utility of eDNA for biodiversity monitoring and conservation. Our findings underscore the potential of eDNA in providing insights into ecological patterns of entire communities and emphasize the need for comprehensive studies addressing the full taxonomic spectrum in tropical freshwater ecosystems.
Keywords: ddc:630